Comparative effects of vitamin and mineral supplements in the management of type 2 diabetes in primary care: A systematic review and network meta-analysis of randomized controlled trials. (February 2023) - Xia, Jiayue; Yu, Junhui; Xu, Hai; Zhou, Yuhao; Li, Hui; Yin, Shiyu; Xu, Dengfeng; Wang, Yuanyuan; Xia, Hui; Liao, Wang; Wang, Shaokang; Sun, Guiju
Abstract: Medical nutrition treatment can manage diabetes and slow or prevent its complications. The comparative effects of micronutrient supplements, however, have not yet been well established. We aimed at evaluating the comparative effects of vitamin and mineral supplements on managing glycemic control and lipid metabolism for type 2 diabetes mellitus (T2DM) to inform clinical practice. Electronic and hand searches for randomized controlled trials (RCTs) were performed until June 1, 2022. We selected RCTs enrolling patients with T2DM who were treated with vitamin supplements, mineral supplements, or placebo/no treatment. Data were pooled via frequentist random-effects network meta-analyses. A total of 170 eligible trials and 14223 participants were included. Low to very low certainty evidence established chromium supplements as the most effective in reducing fasting blood glucose levels and homeostasis model assessment of insulin resistance (SUCRAs: 90.4% and 78.3%, respectively). Vitamin K supplements ranked best in reducing glycated hemoglobin A1c and fasting insulin levels (SUCRAs: 97.0% and 82.3%, respectively), with moderate to very low certainty evidence. Vanadium supplements ranked best in lowering total cholesterol levels with very low evidence certainty (SUCRAs:100%). Niacin supplements ranked best in triglyceride reductions and increasing high-density lipoprotein cholesterol levels with low to very low evidence certainty (SUCRAs:93.7% and 94.6%, respectively). Vitamin E supplements ranked best in reducing low-density lipoprotein cholesterol levels with very low evidence certainty (SUCRAs:80.0%). Our analyses indicated that micronutrient supplements, especially chromium, vitamin E, vitamin K, vanadium, and niacin supplements, may be more efficacious in managing T2DM than other micronutrients. Considering the clinical importance of these findings, new research is needed to get better insight into this issue. Graphical Abstract: ga1 Highlights: Chromium supplements ranked best in reducing FBG levels and HOMA-IR for T2DM. Vitamin K supplements ranked best in reducing HbA1c and fasting insulin levels. Vanadium supplements ranked best in lowering TC levels for T2DM. Niacin supplements ranked best in TG reductions and increasing HDL-c levels. Vitamin E supplements ranked best in reducing LDL-c levels for T2DM.